A Power-Saving algorithm combing power management and power control for multihop IEEE 802.11 ad hoc networks. (9th April 2009) - Liu, Ming; Liu, Ming T.
Power-saving is a major aspect of mobile network research. MAC level power-saving schemes can be classified into two categories. One is power management, which maximises the number of stations that can be put into sleep node. The other is power control, which minimises the transmission power by controlling the transmitting range. In this paper, the proposed algorithm combines and balances both of these schemes to get maximal power conservation. Using power consumption figures measured and reported by other researchers, a simulation of three algorithms has been set up and results are presented.